The (other) China shock and the Brazilian soy boom: Cui bono? - Samuel Siewers (University of Göttingen, Department of Economics, 2025)
Building upon the argument that factor endowments influence distributional outcomes, this paper examines the consequences of the China shock to global food markets for economic inequality in Brazilian municipalities from 1985 to 2020. I propose a new identification strategy that exploits plausibly exogenous variation in demand for soybeans based on fluctuations in the size of the pig stock in China and show that the proceeds of this China-driven agricultural bonanza have been rather unequally distributed. The soy boom has fueled land consolidation and economic inequality, especially in places dominated by large-scale mechanized agriculture. Income gains have been mostly limited to the top deciles of the distribution, while the poorest segments of the population have become worse off. Additionally, there is evidence that the more unequal a municipality, the more deforestation and rural conflict increase as soy expands.
Keywords: D63; F63; O13; Q17; Q56; 330; inequality; soybeans; Brazil; China shock; deforestation; conflict; sustainability; supply chains